Phylogenetic relationships of Shiga toxin-producing Escherichia coli isolated from Peruvian children - Contreras, C. A. (Society for General Microbiology, 2011)
The aim of this study was to determine the prevalence, virulence factors (stx, eae, ehxA and astA) and phylogenetic relationships [PFGE and multilocus sequence typing (MLST)] of Shiga toxin-producing Escherichia coli (STEC) strains isolated from four previous cohort studies in 2212 Peruvian children aged <36 months. STEC prevalence was 0.4 % (14/3219) in diarrhoeal and 0.6 % (15/2695) in control samples. None of the infected children developed haemolytic uraemic syndrome (HUS) or other complications of STEC. stx1 was present in 83 % of strains, stx2 in 17 %, eae in 72 %, ehxA in 59 % and astA in 14 %. The most common serotype was O26 : H11 (14 %) and the most common seropathotype was B (45 %). The strains belonged mainly to phylogenetic group B1 (52 %). The distinct combinations of alleles across the seven MLST loci were used to define 13 sequence types among 19 STEC strains. PFGE typing of 20 STEC strains resulted in 19 pulsed-field patterns. Comparison of the patterns revealed 11 clusters (I–XI), each usually including strains belonging to different serotypes; one exception was cluster VI, which gathered exclusively seven strains of seropathotype B, clonal group enterohaemorrhagic E. coli (EHEC) 2 and phylogenetic group B1. In summary, STEC prevalence was low in Peruvian children with diarrhoea in the community setting. The strains were phylogenetically diverse and associated with mild infections. However, additional studies are needed in children with bloody diarrhoea and HUS.